Metabolism of 7,12,-dimethylbenz(a)anthracene by normal and regenerating rat livers. - Tomsak, R. L. (Nature Publishing Group, 1977)
The in vitro metabolisms of [14C]7,12-dimethylbenz(a)anthracene (DMBA) by post-mitochondrial supernates and microsomes from intact and regenerating rat livers were compared. Both cell fractions from regenerating livers at 48, 72, and 96 h after partial hepatectomy metabolized less [14C]DMBA than similar fractions from intact livers. Prior in vivo treatment with DMBA enhanced metabolism by the cell fractions from both groups, but specific activities of cell fractions from regenerating livers were always about 60% or less of those from intact livers. Thin-layer chromatographic analysis of metabolites formed in incubations using either cell fraction failed to reveal distinct differences between ether-soluble or water-soluble products of similar fractions from intact and regenerating livers. However, highly reproducible differences were found between chromatograms of water-soluble metabolites formed by microsomes and post-mitochondrial supernates in both intact and regenerating livers. Extrapolations from these studies indicate large differences in the metabolic capacity of intact and regenerating livers when expressed on a whole-liver basis, but it is suggested that there may be additional factors contributing to the increased retention of DMBA by regenerating livers.